The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/01.hyp.0000200033.14574.14
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid, Left Ventricular Mass Index, and Risk of Cardiovascular Disease in Essential Hypertension

Abstract: Abstract-Elevated serum uric acid (UA) is frequently encountered in individuals with hypertension, but whether the relationship between UA and cardiovascular events is circumstantial or causal remains to be answered. We examined the association between serum UA and left ventricular mass index (LVMI) and investigated prospectively whether the combination of UA and LVMI can predict the incidence of cardiovascular disease (CVD) in asymptomatic subjects with essential hypertension. A total of 619 subjects (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 54 publications
11
86
0
8
Order By: Relevance
“…In a smaller sample of hypertensive subjects Matsumura et al found the opposite [14]. Iwashima et al, in 619 hypertensive individuals, showed that SUA was independently associated with LVMI [8]. More recently, Mitsuhashi et al reported that SUA was positively associated with electrocardiographically diagnosed LVH in healthy Japanese men [13].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a smaller sample of hypertensive subjects Matsumura et al found the opposite [14]. Iwashima et al, in 619 hypertensive individuals, showed that SUA was independently associated with LVMI [8]. More recently, Mitsuhashi et al reported that SUA was positively associated with electrocardiographically diagnosed LVH in healthy Japanese men [13].…”
Section: Discussionmentioning
confidence: 97%
“…The conflicting findings about the relationships between SUA and LVM seem in part to mirror the controversy on the role of SUA as independent risk factor for CV morbidity and mortality [1,2,8]. Up until today, it is still unclear whether hyperuricemia has a causative role in CVD or, as has been more often suggested, is simply a marker for other risk factors, frequently associated with increased SUA levels, such as hypertension, dyslipidemia, MetS and renal dysfunction [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between hyperuricemia and hypertension has been reported in several studies. [5][6][7][8][9][10][11][12][13]16,17 Among children newly diagnosed with hypertension, serum uric acid was highly correlated with both systolic and diastolic blood pressure. 8 In the Framingham cohort, subjects with hypertension have been noted to have a 3-fold increased risk of gout.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were performed with phased-array echocardiography with M-mode, 2D, pulsed and color-flow Doppler capabilities as previously reported. 24 Left ventricular internal dimension, and septal and posterior wall thickness were measured at end-diastole and end-systole according to the American Society of Echocardiography recommendations. 25 Color-flow Doppler recordings were used to check for aortic and mitral regurgitation, as described previously.…”
Section: Echocardiographic Assessmentmentioning
confidence: 99%